Quranic Refrences in Manuscript Musnawi Ubaidia Kalan - Ul Haq, Ehsan (sourcecoder, 2022)
Persian language is included in the oldest languages in the world. In the Mughal’s rule Persian language is national language of sub continent. During nineteen century in the sub-Continent Mughal’s rule fell down and the British occupied the whole region. British were banned by Persian language but Muslims and especially Muslim saints and Sufis use Persian language for writing work. The same has been done in Multan called the city of saints.Khawaja Ubaid Ullah Multani is one of the prominent Sufi and writer of Multan. He wrote more than 100 books. One of these books is Musnawi Ubaidia Kalan which was written by Him for his elder son Abdul Rehman for advice. In This Musnawi Khawaja Ubaid Ullah Multani uses many references from The Holy Book Quran e Majeed as a proof. With this the importances of this Musnawi also rise. In this article I discuss these Quranic references in details.